Molecular Recognition in C‐Type Lectins: The Cases of DC‐SIGN, Langerin, MGL, and L‐Sectin. (2nd July 2020) - Valverde, Pablo; Martínez, J. Daniel; Cañada, F. Javier; Ardá, Ana; Jiménez‐Barbero, Jesús
Abstract: Carbohydrates play a pivotal role in intercellular communication processes. In particular, glycan antigens are key for sustaining homeostasis, helping leukocytes to distinguish damaged tissues and invading pathogens from healthy tissues. From a structural perspective, this cross‐talk is fairly complex, and multiple membrane proteins guide these recognition processes, including lectins and Toll‐like receptors. Since the beginning of this century, lectins have become potential targets for therapeutics for controlling and/or avoiding the progression of pathologies derived from an incorrect immune outcome, including infectious processes, cancer, or autoimmune diseases. Therefore, a detailed knowledge of these receptors is mandatory for the development of specific treatments. In this review, we summarize the current knowledge about four key C‐type lectins whose importance has been steadily growing in recent years, focusing in particular on how glycan recognition takes place at the molecular level, but also looking at recent progresses in the quest for therapeutics. Abstract : Fine specificity : The interaction of glycans with C‐type lectin receptors (CLRs) mediates the dissemination of infections and is strongly related to the immune response. In this review, we emphasize the molecular recognition features of four of the most studied CLRs of group II: DC‐SIGN, Langerin, MGL and LSECtin